ANTI-SEISMIC STUDY OF WIND TURBINE STRUCTURE BASED ON TMD - LIU ZhongSheng; YANG Yang; LI Chun; ZOU JinHua; TANG JinHua (Jixie qiangdu)
Turbulent winds and earthquakes are the two main factors that lead to the vibration of the wind turbine tower. In order to study the dynamic response characteristics and anti-seismic of wind turbine structure under wind-earthquake coupling condition, NREL 5 MW wind turbine is studied. A soil-structure interaction model was established by Wolf Method, and based on the multi body dynamics simulation and open source software FAST, the seismic load calculation module is developed. The structural control of the wind turbine tower under the seismic condition is carried out by configuring a tuned mass damper（Tuned Mass damper, TMD） at the top of the tower by self-compiling program. The results show that the seismic load greatly increases the lateral vibration of the tower, and the excitation frequency is the first-order lateral natural frequency of the tower. Under the control of TMD, the dynamic response of tower and nacelle are obviously reduced, where the amplitude of lateral displacement of the tower top is reduced by 18%, the standard deviation is reduced by 67%, and the response amplitude of the first order natural frequency of tower is greatly reduced, as high as 90%. Additionally, the variation of the lateral acceleration of the tower top is reduced by 4%, the standard deviation is reduced by 61%, and the peak vibration of the first-order natural frequency decreases by 88%. Therefore, the TMD can be used for anti-seismic of wind turbines in extreme environments such as earthquakes, and improve the stability of wind turbines.